Síntese, caracterização e estudo da reatividade de nitrosilo complexos de rutênio com possível ação citotóxica - Macedo, Dayana Patrícia da Silva Penha (2022)
Nitric oxide is a signaling molecule that has important chemical and biological characteristics for the development of new cytotoxic agents, such as the ruthenium nitrosyl complexes, which in recent decades have shown relevant antitumor activity. These complexes, when receiving a photochemical stimulus, can release NO in the body and thus generate reactive species that destroy target cells, in a treatment known as photodynamic therapy. In this way, the synthesis, characterization and study of the reactivity of nitrosyl complex of the[Ru(bpy)(phen)L(NO)](PF6)4 type is presented, in which L are biological and cationic dyes such as Nile blue and safranin, bpy = 2,2'- bipyridine and phen = 1,10'-phenanthroline. In this work, new precursor complexes were obtained [Ru(bpy)(phen)(NB)Cl](PF6)2 and [Ru(bpy)(phen)(SA)Cl](PF6)2 and the nitrosyl complexes [Ru(bpy)(phen)(NB)NO](PF6)4 and [Ru(bpy)(phen)(SA)NO](PF6)4. According to the electronic spectra, in methanol, it was possible to verify the intraligand bands of dyes, bipyridine and phenantroline, as well as the charge transfer band from the metal to the polypyridine ligands in the region of 420 nm. In the vibrational spectra in KBr pellets, the stretch of NO+ in 1926 and 1938 cm-1 is verified for the complexes with Nile blue and safranin, respectively, indicating that the nitric oxide is coordinated to the metallic center in the linear form. When analyzing the cyclic voltammograms of nitrosyl complexes, in NaTFA 0.1 mol L-1, there is a single almost reversible process related to the NO+/0 redox pair. Regarding the reactivity was done the acid-base equilibrium, noting that at pH 9.4 and 8.6 there is the conversion of nitrosyl to nitrite for the complexes with Nile blue and safranin, in that order. The release of nitric oxide from the coordinating sphere was analyzed by electrochemistry by square wave voltammetry, by photochemical stimulation with red light and by reaction with biological reductants, in alls the release occurs by a chemical reaction that reduces the binding from NO+ to NO0 and due to the weakening of the bond RuII - NO0, this is released.